Beat the heat: Optimizing performance in a less than optimal enviroment - Sleivert, G. (High Performance SIRCuit, 2010)
This article briefly summarises the key factors that limit performance in a hot enviroment and reviews practical strategies for coaches and athletes to optimize performance and training in hot weather. Primarily these strategies are focused upon minimizing the rise in deep body temperature and reducing the strain the budy experiences as a result of exercising in the heat. Advanced preparation is critical and a primary stratcegy is to ensure athletes are aerobically fit, have adapted to exercising in hot conditions through regular and systematic exposure to the heat (heat adaptation), have appropriate clothing to maximize heat loss and protect against solar radiation and understand the venue hot-spots. Even with an aerobic base, individual responses to exercising in the heat vary widely and a key preparation strategy is to evaluate individual differences by simulating the enviroment during training or holding a hot-weather camp. Key factors to monitor include 1) rate of body heating 2) sweat rate and composition 3) thermal tolerance 4) perception of effort and thermal comfort. With these differences identified then countermeasures and strategies can be implemented to optimize an athlete's training and performance. Modifying warm-up and using precooling to reduce heat storage prior to competition are key strategies for enhancing performance in the heat. Additionally, using the information gathered through monitoring it is important to work with athletes on hydration strategies to match sweat and salt losses as best they can and adjust tactics and pacing for the conditions. With sufficient advanced preparation and the adoption of some or all of the acute countermeasures presented in this papers those that struggle with the heat will likely improve both their training and performance. For those that are accustomed to hot weather training, these strategies may provide a small performance edge that makes the difference to getting on the podium.